Preparation and application of a colorimetric film based on sodium alginate/sodium carboxymethyl cellulose incorporated with rose anthocyanins. (1st November 2022) - Yang, Yang; Yu, Xuena; Zhu, Yanling; Zeng, Yan; Fang, Chunshan; Liu, Yu; Hu, Shiwei; Ge, Yaming; Jiang, Wei
Highlights: A colorimetric film was prepared using rose anthocyanins as the indicator. Colorimetric film possessed a sensitive color response to pH and volatile ammonia. Color changes of the colorimetric film reflected the freshness of Penaeus vannamei . Abstract: To monitor the freshness of Penaeus vannamei during storage, a colorimetric film based on sodium alginate/sodium carboxymethyl cellulose incorporated with rose anthocyanins extract (RAE) was prepared. The results showed that the incorporation of RAE increased moisture content, water vapor permeability, and water contact angle of the colorimetric film. FTIR, XRD spectra, and SEM demonstrated that RAE had good compatibility with the film-forming substrate. The colorimetric film presented obvious color variation in the pH range of 2.0–12.0 and was sensitive to volatile ammonia. The colorimetric film exhibited a visual color change from pink to pale yellow to yellowish green during the storage of Penaeus vannamei at 4 °C. Significant correlations were observed between the color change of colorimetric film (ΔE) and the pH value or TVB-N content of Penaeus vannamei ( p < 0.05). Therefore, the colorimetric film shows great application potential to monitor the freshness of shrimp as intelligent packaging.